PERANAN KEPOLISIAN TANAH KARO DALAM UPAYA PENANGGULANGAN DAN KEWENANGAN TERHADAP TINDAK PIDANA NARKOBA (STUDI POLRES TANAH KARO) - Saifullah; Rayani Saragih; Maria Ferba Editya S (Journal Recht (JR), 2022)
This study aims to determine the role of the Tanah Karo Police in efforts to overcome and have authority over drug crimes, to find out what are the obstacles to the Tanah Karo Police in dealing with drug crimes and to find out the efforts of the Tanah Karo Police to enforce the law for drug dealers. The data collection technique used in this research is library research, namely by collecting data and information in the form of books, scientific articles, laws and regulations and data analysis using qualitative analysis, which is an analysis that describes or describes the the efforts made by the Tanah Karo Police in an effort to overcome and have authority over narcotics crimes, carry out socialization about the dangers of narcotics in schools, appeal to and invite youth in positive activities outside school hours and put up banners warning about the dangers of narcotics, the obstacles faced by the drug detective unit at the Tanah Karo Police in dealing with crime. Narcotics crime comes from internal and external obstacles and the efforts of the Tanah Karo Police in enforcing the law for drug dealers, namely by making repressive efforts (actions).